Fundamental gap in fundamental biology - Kordium, V.A.; Andrienko, V.I.; Maslova, O.A.; Shuvalova, N.S.; Irodov, D.M.; Ruban, T.A.; Sukhorada, E.M.; Likhacheva, L.I.; Shpilevaya, S.P. (Вiopolymers and Cell, 2011)
The article raises the problems of intracellular spatial and temporal organization of metabolism, signaling,
and energy supply of these processes. To provide cell functions, the enzymes of metabolic chains, molecules
of signaling pathways, and macroergs (as units of molecular interactions, accompanied by energy
consumption) should find their partners and get their precise spatial relationship. The current views are
based on ideas of compartmentalization of all processes as local sites of cellular matrix membrane, where
specific stages of different metabolic cycles take place. The assembly of complexes of macromolecules in the
number and combinations, required for their adequate functioning in the space of a cell, is generally
described as intracellular transport of vesicles, implemented by mobile elements of cytoske- leton. Inside
the vesicle there is «effective load» – macromolecules. The membranes of these vesicles fuse with specific
sites of the matrix membranes and therefore relocate macromolecules. Neither calcula- tions nor
assumptions allow explaining precise formation of enzymatic chains, their interaction, signaling, etc. on
this basis. Such transport of macromolecules (inside vesicles) enables solving other tasks. The concept of
search-and-address systems in the form of space-scanning micro vesicles is proposed and well-grounded
for purposes of searching for partners, forming chains and complexes, and building compartments. The
micro vesicles collect corresponding chains of enzymes, signaling, and ensure the interactions on their
surface. These micro vesicles are exactly those compartments, which provide for both precision of
processes and their relationship.
Keywords: metabolism, cell, compartmentalization, vesicle, trans- port of macromolecules, precision of
processes. Ставится проблема внутриклеточной пространственно-временной организации метаболизма, сигналинга и энергетического обеспечения этих процессов. Для функционирования клетки ферменты метаболических цепей, молекулы сигнальных путей, макроэрги (как единицы молекулярных взаимодействий,
сопровождающихся поглощением энергии) должны находить своих партнеров и пространственно-прецизионно взаиморасполагаться. Существующие представления основаны на идеях компартментализации всех этих процессов в виде локальных участков мембраны клеточного матрикса, на которых
происходят отдельные этапы различных циклов. Сборка комплексов макромолекул в требуемом количестве и сочетаниях для их адекватного функционирования в пространстве клетки в самом общем виде
описывается как внутриклеточный транспорт везикул, осуществляемый подвижными элементами цитоскелета. А внутри везикул расположен «полезный груз» – макромолекулы. Мембраны таких везикул
сливаются с определенными участками мембран матрикса и таким способом перемещают макромолекулы. Любые расчеты и любые допущения не позволяют на подобной основе объяснить прецизионные
формирования ферментных цепей, их взаимодействие, сигналинг и т. д. Такой транспорт макромолекул (внутри везикул) обеспечивает решение иных задач. Для объяснения поиска партнеров, формирования цепей и комплексов, образования компартментов предлагается и обосновывается концепция поисково-адресных систем доставки в виде сканирующих пространство клетки микровезикул. Они собирают на своей поверхности соответствующие цепи ферментов, участков сигналинга, их взаимодействия. Такие микровезикулы и являются компартментами, обеспечивающими и прецизионность процессов, и их взаимодействие.
Ключевые слова: метаболизм, клетка, компартментализация, везикула, транспорт макромолекул, прецизионность процессов. У публікації поставлено проблему внутрішньоклітинної просторово-часової організації метаболізму, сигналінгу та енергетичного забезпечення цих процесів. Для функціонування клітини ферменти метаболічних ланцюгів, молекули сигнальних шляхів, макроерги (як одиниці молекулярних взаємодій, що супроводжуються поглинанням енергії) повинні знаходити своїх партнерів і мати
просторово-прецизійне взаєморозташування. Існуючі уявлення
засновано на ідеях компартменталізації усіх цих процесів у вигляді локальних ділянок мембрани клітинного матрикса, де відбуваються окремі етапи різних циклів. Збирання комплексів макромолекул у необхідній кількості і комбінаціях для їхнього адекватного функціонування у просторі клітини у самому загальному вигляді описується як внутрішньоклітинний транспорт везикул,
який здійснюється рухливими елементами цитоскелета. А всередині везикул розташований «корисний вантаж» – макромолекули. Мембрани таких везикул зливаються з певними ділянками
мембран матриксу і таким чином пересувають макромолекули.
Будь-які розрахунки і припущення не дозволяють на подібній основіз’ясувати прецизійні формування ферментних ланцюгів, їхню
взаємодію, сигналінг тощо. Такий транспорт макромолекул (усередині везикул) забезпечує вирішення інших завдань. Для пояснення пошуку партнерів, формування ланцюгів і комплексів, створення компартментів пропонується і обгрунтовується концепція
пошуково-адресних систем доставки у вигляді скануючих простір клітини мікровезикул. Вони збирають на своїй поверхні відповідні ланцюги ферментів, ділянок сигналінгу, їхньої взаємодії.
Такі мікровезикули і є компартментами, що забезпечують і прецизійність процесів, і їхню взаємодію.
Ключові слова: метаболізм, клітина, компартменталізація,
везикула, транспорт макромолекул, прецизійність процесів.